Rational Design of Regenerable Amino-Functionalized Fluorescent Covalent Organic Framework for the Exclusive Detection of Mercury(II) - Ren, Yanbiao (Langmuir : the ACS journal of surfaces and colloids, 2024)
Goal-oriented development of novel covalent organic frameworks (COFs) to construct a sensing platform for highly toxic mercury (II, Hg2+) is of tremendous significance. Recently, numerous COFs with sulfur-based ligands were developed for Hg2+ monitoring; however, strong binding of Hg2+ by sulfur makes their regeneration very tough. Herein, we designed and developed an amino-functionalized fluorescent COF (COF-NH2) through facile postmodification for Hg2+ detection in which the π-conjugation skeleton is the signal reader and the nitrogen-based side is the highly selective Hg2+ receptor. More importantly, this nitrogen-based receptor permits the reversible binding of Hg2+. As a sensing platform, the outstanding performance of COF-NH2 for Hg2+ detection was reached with respect to high sensitivity with an ultralow detection of 15.3 nM, real-time response with rapid signal change of 10 s, and facile visualization with significant fluorescence color change. Expectedly, COF-NH2 obtained facile recycling which still shows excellent response performance toward Hg2+ after six cycles based on the reversible interaction between amino groups and Hg2+. Our work not only shows an attractive foreground of fluorescent COF for Hg2+ detection but also emphasizes the easy construction of novel COF materials via the rational introduction of metal ligands for the recognition of other metal ions